Blackwell Handbook of Social Psychology : Group Processes. - Hogg, Michael (Blackwell handbook of social psychology., 2007)
This handbook provides an overview of the social psychology of group processes. The topics covered include group decisions, juries, leadership, group remembering, roles, status, social identity and group membership, socialization, negotiation and bargaining, emotion and mood, and crowd behaviour.